2002
DOI: 10.1523/jneurosci.22-02-00396.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of T-Type Calcium Channels by Neuroleptics

Abstract: T-type calcium channels play critical roles in cellular excitability and have been implicated in the pathogenesis of a variety of neurological disorders including epilepsy. Although there have been reports that certain neuroleptics that primarily target D2 dopamine receptors and are used to treat psychoses may also interact with T-type Ca channels, there has been no systematic examination of this phenomenon. In the present paper we provide a detailed analysis of the effects of several widely used neuroleptic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
178
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(187 citation statements)
references
References 51 publications
5
178
1
3
Order By: Relevance
“…Cloned T-type channels were blocked with EC 50 values around 30-50 nM (Santi et al, 2002), whereas native channels were blocked with EC 50 B500 nM (Enyeart et al, 1993;Arnoult et al, 1998). In the present study, 500 nM pimozide inhibited 85% of the Ca 2 þ response to 75 mM K þ (Figure 5c and d).…”
Section: Lj Jensen Et Almentioning
confidence: 99%
“…Cloned T-type channels were blocked with EC 50 values around 30-50 nM (Santi et al, 2002), whereas native channels were blocked with EC 50 B500 nM (Enyeart et al, 1993;Arnoult et al, 1998). In the present study, 500 nM pimozide inhibited 85% of the Ca 2 þ response to 75 mM K þ (Figure 5c and d).…”
Section: Lj Jensen Et Almentioning
confidence: 99%
“…Clinically, flunarizine is known as Sibeliumt and has been widely used to treat the clinical disorders, including vertigo, migraine, epilepsy, and tinnitus. 12 Recently, it is known to protect the perfused rat liver cells from ischemia with reperfusion and neurons from serum deprivation, nerve growth factor deprivation, oxidative stress, and axotomy, respectively. 13 Previously, we reported that flunarizine attenuated the cisplatin-induced apoptosis of auditory cells through inhibition of lipid peroxidation and mitochondrial permeability transition.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of drug binding sites that have been characterized surround the channel pore, involving the fifth and sixth transmembrane helices, or they lie within the permeation pathway (reference 35 and references therein). Although there is no structural information regarding the precise binding site of flunarizine, it is well established that this neuroleptic is used to treat migraine (36) and vertigo (37) and that it inhibits all three T-type Ca 2ϩ channels (38). Moreover, a moderate antagonistic activity toward dopamine receptors was reported (38).…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
“…Although there is no structural information regarding the precise binding site of flunarizine, it is well established that this neuroleptic is used to treat migraine (36) and vertigo (37) and that it inhibits all three T-type Ca 2ϩ channels (38). Moreover, a moderate antagonistic activity toward dopamine receptors was reported (38). Thus, all of the abovementioned drugs have in common the fact that they inhibit cellular transmembrane proteins with multiple transmembrane helices.…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
See 1 more Smart Citation